1989
DOI: 10.1002/1520-6629(198910)17:4<330::aid-jcop2290170406>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Life stressors and coping: A longitudinal analysis among depressed and nondepressed adults

Abstract: This article examines the interrelation between negative life events, ongoing life strains, and coping responses in a longitudinal study of clinically depressed and healthy adults. A two‐wave, two‐variable panel regression analysis revealed moderate stability of both life stressors and coping over a 1‐year interval. The connections between life stressors and coping varied by group status and across specific types of stressors and modes of coping. For depressed persons, there was a relatively strong association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 13 publications
3
26
0
Order By: Relevance
“…Investigators have found that problem-solving coping generally decreases as depressive symptoms increase in Caucasian adults (Billings & Moos, 1984; Fondacaro & Moos, 1989). Nevertheless, samples of depressed Caucasian women have reported problem-focused strategies such as Confrontive Coping and Accepting Responsibility for managing depressive symptoms (Folkman & Lazarus, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have found that problem-solving coping generally decreases as depressive symptoms increase in Caucasian adults (Billings & Moos, 1984; Fondacaro & Moos, 1989). Nevertheless, samples of depressed Caucasian women have reported problem-focused strategies such as Confrontive Coping and Accepting Responsibility for managing depressive symptoms (Folkman & Lazarus, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…One interpretation is that a relationship characterized by low marital quality reflects that one’s spouse is less available as a source of social support for dealing with ones’ own or his or her partner’s symptoms, thereby maintaining or exacerbating the positive relation between spouses’ depressive symptoms over time. Moos and colleagues found that individuals with supportive families engaged in more adaptive coping strategies when faced with stressors that may buffer them from mental and physical illness (Fondacaro & Moos, 1989; Holahan, Moos, & Bonin, 1999). On the other hand, results are not consistent on these relations.…”
Section: Discussionmentioning
confidence: 99%
“…Active coping strategies have been associated with the ability to manage stressful situations, fewer psychological symptoms, and improved well‐being among at‐risk children, 19 college students, 20 traumatized and depressed adults, 21 and patients with a variety of medical conditions 22 . Active coping strategies have been associated with reduced stress‐related symptoms in Gulf War veterans 23 .…”
Section: Relevant Psychological Constructs Associated With Resiliencementioning
confidence: 99%